History and Theology in the Gospels Seventh International East-West Symposium of New Testament Scholars, Moscow, September 26 to October 1, 2016 - Niebuhr, Karl-Wilhelm; Nicklas, Tobias; Seleznev, Mikhail; König, Judith; Draughon, Rebecca; Draughon, Rebecca (Mohr Siebeck, 2020)
Geschichte und Theologie in den Evangelien. Siebtes Internationales Ost-West Symposium der Neutestamentler, Moskau, 26. September bis 1. Oktober 2016.
PublicationDate: 20201029
Keywords: New Testament Theology -- Öffentlich-private Partnerschaft -- Conflict of Laws -- Gospel literature -- historical approaches to the New Testament -- Orthodox Hermeneutics -- Vorteilsausgleichung -- Neues Testament -- Kirchengeschichte -- New Testament -- Church History